Distillate flux enhancement in the air gap membrane distillation with inserting carbon-fiber spacers. Issue 18 (12th December 2017) - Ho, Chii-Dong; Chen, Luke; Huang, Mei-Chih; Lai, Jing-Yuan; Chen, Yu-An
ABSTRACT: A new design of air gap membrane distillation (AGMD) with inserting carbon-fiber spacers with various hydrodynamic angles in flow channels for eddy promoting under concurrent-flow operations was developed theoretically and experimentally. Attempts to enlarge eddy flow in aiming to reduce the temperature polarization were achieved with the inserted carbon-fiber spacers that enhance the heat and mass transfer in the AGMD system. A mathematical model considering heat and mass transfer mechanisms has been developed, and the Nusselt number was correlated with the experimental data. The effects of various operation parameters on the distillate flux enhancement were studied as compared to the modules without inserting carbon-fiber spacers (empty channels).